F.A.D.S rollerable owning / Abdussalam Zulkifli ... [et al.] - Zulkifli, Abdussalam; Mohd Alias, Asraf; Dahalan, Dzulkarnain; Tamsir, Mohammad Faizol (2004)
Hence, we after studying all the aspect in making a useful product, we've choose to make "F.A.D.S Rollerable Owning". F.A.D.S. stands for the initial of the first of our group members. We took this project because we feel it is one of the useful product manufactured in the present market. Not only is it cheap but easy to produce. This will give an advantage to the manufacturer. F.A.D.S. RoUerable Owning not only can be use at home but also at restaurant, shop lots or any commercial premises.